Digital Transformations of Illicit Drug Markets: Reconfiguration and Continuity. By Tzanetakis Meropi and South Nigel (eds) (Emerald, 2023, 183pp., open access) - Gustavsson, Tove (British Journal of Criminology, 2024)
Digital Transformations of Illicit Drug Markets: Reconfiguration and Continuity is authored by leading experts in the field of illicit drug sourcing, who draw on their interdisciplinary backgrounds to illustrate how modern technologies are embedded within our social structures. Since the digital (r)evolution, the sourcing of illicit drugs now takes place through smartphones, encryption, social media platforms and cryptocurrencies. As such this book focusses on these types of retail drug distribution (6). The book compromises contributions from 16 authors across 10 chapters and is organized into 3 distinct sections: ‘The Embeddedness of Digital Drug Markets’, ‘Understanding Drug Demand Online’ and ‘Power Relations’. In the introductory chapter, editors Tzanetakis and South invite readers to delve into the digital transformation of society and its impact on the drug trade. They emphasize the significance of social relationships within digital illicit markets and expand upon existing social science research in this field. The editors advocate for a nuanced examination of these social dynamics and provide an overview of the technological architecture underpinning digital illicit markets. Additionally, they define the infrastructural characteristics of cryptomarkets, including the embedded reputational systems while at the same time posing critical questions of what the state role ought to be in our digital age.